DEVELOPING STUDENTS' WRITING ABILITY THROUGH READING TO LEARN PROGRAM (A Case Study in One Polytechnic in Bandung) - Khaerunnisa, - (2014)
This study implemented a qualitative data analysis which observed the nature of the implementation of Reading to Learn program in EFL context in Indonesia, as an attempt to develop the students' reading and writing ability in factual text. Specifically, the type of case used in this study was text analysis since the study investigated written text (Merriam, 1991; Travers, 2001; Samanhudi, 2011). The study was conducted and involved 15 second grade of Polytechnic students in Bandung. The data were collected through classroom observations, students' writing texts, and interviews. The data from classroom observations were analyzed through interaction moves (Rose, 2008) and students' writing texts were analyzed through the schematic structures and the linguistic features and the fourteen assessment writing criteria- Genre, Field, Tenor, Mode, Phases, Lexis, Conjunction, Reference, Appraisal, Grammar, Spelling, Punctuation, Presentation, and Layout, proposed by David Rose (2008). The data from all sources were triangulated. The study revealed three findings related to the research questions. First, results of the text analysis showed that the students improved the writing skills at the level of schematic structure and linguistic features, but some students needed more intensive support at the level of linguistic features. Second, as the interview data revealed, students' inability occurred due to their limited knowledge of the wordings in writing especially in the factual text. Regarding to the implementation of Reading to Learn program, the students responded positively, and the positive response appeared to be one of the factors which made the students improve the writing skills. Finally, the findings above suggest that the students need more intensive support and guidance in writing process. It is recommended that Reading to Learn program be implemented at the site, so the students have a better understanding in writing factual text. Besides that, further research in Reading to Learn program is expected to deal with more texts, more intensive support and longer time in conducting the research. Keywords: Reading to Learn Program, factual text, fourteen assessment writing criteria, texts analyses.